Comparative Analysis of the VA/Kaiser and NLM CORE Problem Subsets: An Empirical Study Based on Problem Frequency - Wright, Adam (American Medical Informatics Association, 2011)
The problem list is a critical component of the electronic medical record, with implications for clinical care, provider communication, clinical decision support, quality measurement and research. However, many of its benefits depend on the use of coded terminologies. Two standard terminologies (ICD-9 and SNOMED-CT) are available for problem documentation, and two SNOMED-CT subsets (VA/KP and CORE) are available for SNOMED-CT users. We set out to examine these subsets, characterize their overlap and measure their coverage. We applied the subsets to a random sample of 100,000 records from Brigham and Women’s Hospital to determine the proportion of problems covered. Though CORE is smaller (5,814 terms vs. 17,761 terms for VA/KP), 94.8% of coded problem entries from BWH were in the CORE subset, while only 84.0% of entries had matches in VA/KP (p<0.001). Though both subsets had reasonable coverage, CORE was superior in our sample, and had fewer clinically significant gaps.